Relação entre o torque de rotação lateral do quadril e a cinemática do pé - Thales Rezende de Souza (2012)
Alterations of pronation-supination motion and posture of the foot-ankle complex, in closed chain, have been associated with the occurrence of musculoskeletal disorders. Traditionally, foot kinematics in activities as walking, standing and running is solely attributed to distal mechanical variables, such as alignment and mobility of the foot. However, the mechanics of the hip, in the transverse plane, can also influence foot kinematics. Theoretical propositions indicate that greater hip externalrotation moment, or greater hip stiffness (related to this external rotation moment) would lead to less foot pronation. The objectives of this thesis were: (a) to investigate whether the interaction of hip passive stiffness, related to the external-rotation moment, with the alignment and mobility of the foot-shank complex predicts rearfoot kinematics, during walking and standing; (b) to investigate whether increases in hipexternal-rotation moment, obtained with the use of elastic bands, decreases pronation of the foot-ankle complex, during walking. A first study was conducted to investigate the reliability of a kinematic method in which the positions of the shank, calcaneus and forefoot were measured with clusters of tracking markers. Angles between the calcaneus and the shank, between the forefoot and the calcaneus, and between the forefoot and the shank were calculated during the stance phase of walking and during standing with the subtalar joint in neutral position. Ten asymptomatic participants were assessed on two occasions, one week apart. The test-retest reliabilities (intraclass correlation coefficients) of variables obtained from the angles ranged from 0.76 to 0.93, which was considered appropriate. In a second study, hip passive stiffness and the combination of bone alignment and mobility of the foot-ankle complex were assessed with clinical measures, in 23 asymptomaticparticipants. Multiple linear regression analyses were performed to investigate whether the interaction of these variables predicts the eversion-inversion of the rearfoot during the stance phase of walking and bipedal relaxed standing. It was found that these variables explained 27% to 40% of the variability of rearfoot kinematics (p!0.041). In a third study, hip external-rotation moment was increased by means of elastic bands of low or high stiffness, on 17 asymptomatic participants. The angles between calcaneus and shank, between forefoot and calcaneus and between forefoot and shank were measured during the stance phase of walking. The curves of these angles were compared using the confidence intervals (95%), point-by-point. The use of both elastic bands produced a significant reduction in the eversion of thecalcaneus relative to the shank and a significant increase in the eversion of the forefoot relative calcaneus and relative to shank, which showed a reduction of footpronation. The results of this thesis indicate that the proximal mechanics of the lower limb, in the transverse plane, influences pronation-supination of the ankle-foot complex, during walking and upright posture. The external-rotation moment of the hip should be considered during the assessment and intervention of individuals with altered pronation-supination behavior.